Is the Width of a Surgical Margin Associated with the Outcome of Disease in Patients with Peripheral Chondrosarcoma of the Pelvis? A Multicenter Study. Issue 11 (November 2019) - Tsuda, Yusuke; Evans, Scott; Stevenson, Jonathan D; Parry, Michael; Fujiwara, Tomohiro; Laitinen, Minna; Outani, Hidetatsu; Jeys, Lee
Abstract: Background: We attempted to resect peripheral chondrosarcoma of the pelvis with clear margins. Because of the proximity of vessels or organs, there is still concern that narrow surgical margins may have an adverse effect on disease outcomes. Although current guidelines recommend resection of histologic Grade II or Grade III chondrosarcomas with a "wide" margin, there are no specific recommendations for the adequate width of a surgical margin. Questions/purposes: (1) What is the disease-specific and local recurrence-free survival of patients with peripheral chondrosarcoma of the pelvis treated with resection or amputation? (2) Is the width of a surgical margin associated with the outcome of disease in patients with peripheral chondrosarcoma of the pelvis? (3) Does the histologic grade as determined with a preoperative biopsy correlate with the final grade after resection? (4) What are surgical complications in these patients? Methods: We retrospectively reviewed records from three international collaborating hospitals. Between 1983 and 2017, we resected 262 pelvic chondrosarcomas of all types. After reviewing the pathologic reports of these patients, we included 52 patients with peripheral chondrosarcomas of the pelvis who had an osteochondroma-like lesion at the base of the tumor and a cartilage cap with malignant cells in resected specimens. To be eligible for this study, a patient had to have a minimum of 1 year of follow-up. Two patients were excluded because they had less than 1 year of follow-up, leaving 50 patients for inclusion in this study. The median follow-up duration was 7.0 years (interquartile range 2.1-10 years). The median age was 37 years (IQR 29-54 years). The ilium was the most frequently affected bone (in 36 of 50 patients; 72%). The histologic status of the surgical margin was defined as microscopically positive (0 mm), negative < 1 mm, or negative ≥ 1 mm. Thirteen of the 50 patients (26%) had local recurrence. Seven of 34 patients had Grade I tumors, five of 13 had Grade II tumors, and one of three had a Grade III tumor. Nine of 16 patients had multiple local recurrences. Two patients with Grade I tumors and two with Grade II tumors died because of pressure effects caused by local recurrence. Results: The 10-year disease-specific and local recurrence-free survival rates were 90% (95% confidence interval, 70-97) and 69% (95% CI, 52-81), respectively. A surgical margin ≥ 1 mm (n = 16) was associated with a better local recurrence-free survival rate than a surgical margin < 1 mm (n = 17) or 0 mm (n = 11) (10-year local recurrence-free survival: resection margin ≥ 1 mm = 100% versus < 1 mm = 52% [95% CI, 31 to 70]; p = 0.008). No patients with a surgical margin ≥ 1 mm had local recurrence, metastasis, or disease-related death, irrespective of tumor grade. Patients with local recurrence (n = 13) showed worse disease-specific survival than those without local recurrence (n = 37) (10-year disease-specific survival: local recurrence [+] = 59% [95% CI, 16 to 86] versus local recurrence [-] = 100%; p=0.001]). The preoperative biopsy results correctly determined the tumor grade in 15 of 41 patients (37%). The most frequent complication after surgery was local recurrence (13 of 50 patients, 26%). Deep infection was the most frequent nononcologic complication (four patients). Conclusions: We found a high local recurrence rate after surgical treatment of a peripheral pelvic chondrosarcoma, which was related to the width of the surgical margin. These local recurrences led to inoperable recurrent tumors and death. The tumor grade as determined by preoperative biopsy was inaccurate in 2/3 of patients compared with the final histologic assessment. Therefore, we believe every attempt should be made to achieve a negative margin during the initial resection to lessen the likelihood of local recurrence of peripheral chondrosarcoma of the pelvis of all grades. A margin of 1 mm or more appeared to be sufficient in these patients. Level of Evidence: Level III, therapeutic study.